Gender Pay Gap and Cultural Values - Burns, Natasha; Minnick, Kristina; Netter, Jeffry; Starks, Laura (Journal of Financial and Quantitative Analysis, 2026)
Abstract Employing a cross-country sample, we examine how a population’s underlying cultural values help explain gender compensation variation across corporate executives. The results show that the cultural differences, embedded in societies long before the board’s compensation decisions, have significant explanatory power for the observed gender gap in executive compensation. Using an Oaxaca–Blinder decomposition combined with variables previously shown to be fundamental determinants of executive compensation, we find that adding cultural measures increases the model’s explanatory power of the gender compensation gap from 44% to 95%. We use further identification strategies to support causal inference.